Leptospiral Proteins Recognized during the Humoral Immune Response to Leptospirosis in Humans - Guerreiro, Hygia (American Society for Microbiology, 2001)
Leptospirosis is an emerging zoonosis caused by pathogenic spirochetes belonging to the genus Leptospira. An understanding of leptospiral protein expression regulation is needed to develop new immunoprotective and serodiagnostic strategies. We used the humoral immune response during human leptospirosis as a reporter of protein antigens expressed during infection. Qualitative and quantitative immunoblot analysis was performed using sera from 105 patients from Brazil and Barbados. Sera from patients with other diseases and healthy individuals were evaluated as controls. Seven proteins, p76, p62, p48, p45, p41, p37, and p32, were identified as targets of the humoral response during natural infection. In both acute and convalescent phases of illness, antibodies to lipopolysaccharide were predominantly immunoglobulin M (IgM) while antibodies to proteins were exclusively IgG. Anti-p32 reactivity had the greatest sensitivity and specificity: positive reactions were observed in 37 and 84% of acute- and convalescent-phase sera, respectively, while only 5% of community control individuals demonstrated positive reactions. Six immunodominant antigens were expressed by all pathogenic leptospiral strains tested; only p37 was inconsistently expressed. Two-dimensional immunoblots identified four of the seven infection-associated antigens as being previously characterized proteins: LipL32 (the major outer membrane lipoprotein), LipL41 (a surface-exposed outer membrane lipoprotein), and heat shock proteins GroEL and DnaK. Fractionation studies demonstrated LipL32 and LipL41 reactivity in the outer membrane fraction and GroEL and DnaK in the cytoplasmic fraction, while p37 appeared to be a soluble periplasmic protein. Most of the other immunodominant proteins, including p48 and p45, were localized to the inner membrane. These findings indicate that leptospiral proteins recognized during natural infection are potentially useful for serodiagnosis and may serve as targets for vaccine design.